PROCESSOS DE EXCLUSÃO PELA MATEMÁTICA: enunciados de alunos e alunas do Ensino Médio Integrado e do Ensino Superior - Ricardo Gomes Assunção (2022)
This doctoral thesis has been developed in the Post-Graduation Program in Mathematics Education (PPGEduMat), at the Federal University of Mato Grosso do Sul (UFMS), and aims to study the processes of exclusion in mathematics, describing how students constitute themselves as subjects excluded by the mathematics curriculum. For this, narrative interviews were made with male and female students from the Federal Institute of Education, Science and Technology Goiano - Campus Urutaí, who were taking the probation in mathematics, in Integrated High School courses (Ensino Médio Integrado - EMI), and evaded from the course of Mathematics Licenciature. The specialized research corpus is formed by textualizations, produced from the referred interviews, 4 of them from EMI and 10 from Graduation. The corpus was analyzed by means of Discourse Analysis, in the Foucauldian perspective, highlighting enunciations about what was said by the students, with the purpose of understanding how they constitute themselves as subject-students, in relation to the subject position that suffered exclusion processes by mathematics. From the analyses, three statements were constructed: "If I had tried harder, I would succeed", related to neoliberal and religious discourses, in which the subject-student places herself in the position of responsible, guilty for her own process of exclusion by mathematics; "Women have to take care of others, before taking care of themselves', linked to patriarchal, religious and feminist discourses, in which the subject-student places herself in the position of caregiver, which collaborates to the evasion in the Mathematics Degree course; and "It wasn't the mathematics I expected", linked to scientific and pedagogical-educational discourses, in which the subject-student places herself in the position of blaming Eurocentered mathematics as the responsible for her exclusion process. After the analyses, it was possible to describe how the students, who participated in the research, constitute themselves as student-subjects excluded by the mathematics curriculum. The research also contributed to the construction of a diagnosis of the present, concerning the processes of exclusion by mathematics, in courses of a Federal Institute, located in the interior of Brazil, showing how neoliberal, religious, patriarchal, feminist, scientific and pedagogical-educational discourses operate through mathematics, resulting in exclusions.